2022
DOI: 10.1038/s41598-022-15625-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major photodegradant in metronidazole by LC-PDA-MS and its reveal in compendial methods

Abstract: Metronidazole in aqueous solution is sensitive to light and UV irradiation, leading to the formation of N-(2-hydroxyethyl)-5-methyl-l,2,4-oxadiazole-3-carboxamide. This is revealed here by liquid chromatography with tandem photo diode array detection and mass spectrometry (LC-PDA-MS) and further verified by comparison with the corresponding reference substance and proton nuclear magnetic resonance (1H-NMR). However, in current compendial tests for related substances/organic impurities of metronidazole, the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Verma et al [16] using HPLC found five degradation products in a sample of metronidazole in hydrogen peroxide after 48 h, which is consistent with the results obtained in this work. Chen et al [35] in a sample of metronidazole after photodegradation, using the LC-PDA-MS technique, also found the presence of five of its degradation products. Therefore, the proposed TLC-densitometry method is selective in relation to the analysis of metronidazole.…”
Section: Stability Of Metronidazole In Solutionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Verma et al [16] using HPLC found five degradation products in a sample of metronidazole in hydrogen peroxide after 48 h, which is consistent with the results obtained in this work. Chen et al [35] in a sample of metronidazole after photodegradation, using the LC-PDA-MS technique, also found the presence of five of its degradation products. Therefore, the proposed TLC-densitometry method is selective in relation to the analysis of metronidazole.…”
Section: Stability Of Metronidazole In Solutionsmentioning
confidence: 95%
“…Metronidazole Secnidazole The study of the stability of metronidazole, secnidazole, ornidazole, and tinidazole has been the subject of numerous scientific papers . Various analytical techniques were used to analyze the stability of 5-nitroimidazoles: high-performance liquid chromatography (HPLC) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], ultra-performance liquid chromatography (UPLC) [33,34], liquid chromatography with mass spectrometry (LC-MS) [25], liquid chromatography with tandem photo diode array detection and mass spectrometry (LC-PDA-MS) [35], UV- The study of the stability of metronidazole, secnidazole, ornidazole, and tinidazole has been the subject of numerous scientific papers . Various analytical techniques were used to analyze the stability of 5-nitroimidazoles: high-performance liquid chromatography (HPLC) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], ultra-performance liquid chromatography (UPLC)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation